2002
DOI: 10.1074/jbc.m111833200
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Mutagenesis and Immunochemical Analysis of Visual Arrestin Interaction with Rhodopsin

Abstract: Visual arrestin inactivates the phototransduction cascade by specifically binding to light-activated phosphorylated rhodopsin. This study describes the combined use of insertional mutagenesis and immunochemical approaches to probe the structural determinants of arrestin function. Recombinant arrestins with insertions of a 10-amino acid c-Myc tag (EQKLISEEDL) were expressed in yeast and characterized. When the tag was placed on the C terminus after amino acid 399, between amino acids 99 and 100 or between resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Several studies using a variety of methods including truncation mutagenesis (7,20), differential chemical modification and H/D exchange (21), site-directed mutagenesis (8,9,(22)(23)(24), construction of chimeric arrestins (15,19), peptide competition (25,26), and epitope insertion (27) have shown that arrestin elements important for receptor binding are localized to the concave surfaces of both arrestin domains (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using a variety of methods including truncation mutagenesis (7,20), differential chemical modification and H/D exchange (21), site-directed mutagenesis (8,9,(22)(23)(24), construction of chimeric arrestins (15,19), peptide competition (25,26), and epitope insertion (27) have shown that arrestin elements important for receptor binding are localized to the concave surfaces of both arrestin domains (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data along with the localization of receptor-binding arrestin elements on the concave sides of both domains (Kieselbach et al, 1994;Ohguro et al, 1994;Pulvermuller et al, 2000;Dinculescu et al, 2002;Vishnivetskiy et al, 2004) (Fig. 7) lead to the following model of arrestin binding to the phosphorylated ligand-activated receptor (P-R*) (Gurevich & Gurevich, 2004) (Fig.…”
Section: The Molecular Mechanism Of Arrestin Activationmentioning
confidence: 99%
“…Arrestin elements involved in receptor binding have been identified by a variety of methods, including mutagenesis (Gurevich & Benovic, 1992Gurevich et al, 1994;Gurevich & Benovic, 1995Gurevich, 1998;Vishnivetskiy et al, 1999Vishnivetskiy et al, , 2000, chimera construction (Gurevich et al, 1993aVishnivetskiy et al, 2004), peptide inhibition (Kieselbach et al, 1994;Pulvermuller et al, 2000), differential chemical modification and hydrogen/deuterium exchange , and epitope insertion (Dinculescu et al, 2002). Collectively, these data implicate a substantial portion of the arrestin surface in receptor interaction: most of the concave sides of both domains and a few additional elements (Fig.…”
Section: Receptor Elements Implicated In Arrestin Bindingmentioning
confidence: 99%
“…For in vitro studies, a His (6) tag was incorporated by PCR at the 5′ end of the cDNA immediately after the initiating ATG for xAr-GFP and xAr-myc-GFP, and then cloned into the shuttle vector pPIC-ZA for heterologous expression in Pichia pastoris (Dinculescu et al 2002). Expressed proteins were purified over nickel-agarose (Ni-NTA, Qiagen), followed by heparin agarose.…”
Section: Myc-tagged Arrestinmentioning
confidence: 99%
“…To corroborate and extend these findings, we analyzed the translocation of arrestin in transgenic Xenopus that expressed an arrestin that is unable to bind light-activated phosphorhodopsin (R*P). In previous studies, we demonstrated that binding of arrestin to R*P could be blocked by inserting a ten amino acid myc tag (EQKLISEEDL) in a loop of bovine arrestin between Leu-77 and Ser-78 (Dinculescu et al 2002). Reasoning that this variant of arrestin could be used to address the necessity of arrestin binding to R*P for translocation, we created a homologous substitution in our Xenopus arrestin-GFP fusion, inserting the myc tag between Leu-76 and Thr-77 (xAr-myc-GFP).…”
Section: Is Binding To Light-activated Rhodopsin Required For Arrestimentioning
confidence: 99%